Makna salib Kristus dalam kekristenan menurut Hilarion Alfeyev dalam tradisi Gereja Orthodox - gulo, Mainyer (Davar : Jurnal Teologi, 2024)
ABSTRACT            This research is a concept of understanding the cross of Christ according to the teachings of Hilarion Alfeyev in the tradition of the Orthodox Church. This research uses a qualitative method, in which the author collects data and information from various sources, for example: through books, journals, and other sources that are relevant to the topic according to the concept of Hilarion Alfeyev's teachings in the Orthodox Church tradition. The cross is generally known as a place of torture, where people who commit crimes (hanged on the cross). Jesus Christ who did not evil, was sentenced to the cross for the sins of mankind. Christ had to be willing to suffer and accept all humiliations for the sake of human salvation. Christ took all the punishments so that mankind would not perish. After this event, Christians no longer considered the cross as a place of punishment or torture, but as a place where humans get salvation. Thus, over time, Christians have made the cross a rite in a worship or as a sacred object in remembrance Christ's sacrifice for mankind. Keywords: Cross, Hilarion Alfeyev, Death of Christ, Salvation, Eschatology. ABSTRAKPenelitian ini merupakan konsep tentang pemahaman salib Kristus menurut ajaran Hilarion Alfeyev dalam tradisi Gereja Ortodox. Penelitian ini menggunakan metode kualitatif, yaitu penulis mengumpulkan data dan informasi dari berbagai sumber, misalnya: melalui buku, jurnal, dan sumber lain yang sesuai dengan topik sesuai konsep ajaran Hilarion Alfeyev dalam tradisi Gereja Ortodox. Salib secara umum dikenal sebagai tempat penyiksaan, tempat orang yang berbuat kejahatan (di gantung diatas kayu salib). Yesus Kristus yang tidak berbuat jahat, namun dijatuhkan hukuman salib karena dosa-dosa manusia. Kristus harus rela menderita dan menerima segala hinaan demi keselamatan manusia. Kristus mengambil segala hukuman supaya manusia tidak binasa. Setelah peristiwa tersebut orang-orang Kristen tidak menganggap lagi salib sebagai tempat penghukuman ataupun penyiksaan, melainkan sebagai tempat dimana manusia mendapatkan keselamatan. Dengan demikian seiring berjalannya waktu, orang-orang Kristen menjadikan salib sebagai ritus dalam sebuah ibadah ataupun sebagai benda suci dalam mengingat akan pengorbanan Kristus bagi umat manusia. Kata kunci: Salib, Hilarion Alfeyev, Kematian Kristus, Keselamatan, Eskatologis.